Improved cognitive function in patients with major depressive disorder after treatment with vortioxetine: A EEG study. Issue 1 (10th December 2021) - Kim, Hong; Baik, Seung Yeon; Kim, Yong Wook; Lee, Seung‐Hwan
Abstract: Introduction: Vortioxetine has a positive effect on cognitive function in patients with major depressive disorder (MDD). This study aimed to examine the changes in cognitive function and EEG (spectral power and mismatch negativity (MMN)) in patients with MDD pre‐ and postvortioxetine treatment. Methods: Thirty patients with MDD were included in the study. They were given vortioxetine (10‐20mg po per day) for eight weeks. Depression and anxiety severities, social function (Korean version of the social adjustment scale (K‐SAS)), and cognitive function (digit‐symbol substitution Test (DSST), Korean version of the attentional control questionnaire (K‐ACQ), and Korean version of the perceived deficits questionnaire for depression (K‐PDQD)) were evaluated. Spectral power of EEG and MMN was also measured pre‐ and postvortioxetine treatment. Results: Depression and anxiety severity, social function, and cognitive functioning significantly improved after vortioxetine treatment. Also, there was a significant decrease in the right central delta band and an increase in the right central beta 2 band following vortioxetine treatment. The changes in EEG spectral power were not related to changes in cognitive functions. Baseline MMN significantly predicted changes in DSST score after controlling for the baseline clinical variables. Conclusion: Vortioxetine treatment improved cognitive function and induced changes in EEG (decreased theta power and increased beta power) in patients with MDD. Our results suggest that greater negative MMN amplitude is associated with greater potential for cognitive improvement following vortioxetine treatment. Abstract : BLURB FOR ETOC:Vortioxetine treatment improved cognitive function and induced changes in EEG (decreased theta power and increased beta power) in patients with MDD. Our results suggest that greater negative MMN amplitude is associated with greater potential for cognitive improvement following the vortioxetine treatment.